REPOSITIONING SCHOOL FINANCE CONTROL AS A CATALYST FOR EFFECTIVE ADMINISTRATION OF PUBLIC SENIOR SECONDARY SCHOOLS IN RIVERS STATE (Scientific Journal of Educational Management, Research and law, 2026)
This paper investigates the repositioning of school finance control as a catalyst for effective administration of public senior secondary schools in Rivers State, Nigeria. The study explores critical finance control strategies including budgetary planning and allocation, auditing and financial monitoring, cost-benefit analysis, transparent procurement processes, monitoring of school fees collection, and financial policy compliance. Drawing on existing literature and theoretical perspectives, the paper identifies challenges such as poor financial oversight, delayed fund disbursement, and lack of principal capacity as major hindrances to effective school administration. The paper argues that robust and transparent financial control mechanisms are essential for enhancing administrative efficiency, ensuring judicious use of resources, and improving the overall quality of education. The study suggests that digital transformation of financial processes, capacity building for school leaders, stronger stakeholder engagement, and stricter enforcement of financial policies. It concludes that repositioning financial control systems is a strategic step toward sustainable educational development in Rivers State.